Detection of Financial Statement Fraud by Using the Beneish Ratio Index in Health and Pharmaceutical Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2020 – 2022 - Setiana, Siti Anisah; Dewi, Kusuma (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
The aim of this research is to determine the number of health and pharmaceutical sector companies listed on the Indonesia Stock Exchange which are classified as manipulator, non manipulator, and grey company by using the method Beneish Ratio Index The object of this research is health and pharmaceutical sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling technique used purposive sampling where the sample is determined based on certain criteria determined by the author. The data analysis technique used is quantitative descriptive analysis using Beneish Ratio Index. The variables in this research are Days Sales In Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), and Total Accrual To Total Assets Index (TATA). The results of this research indicate that there are no companies in the health and pharmaceutical sectors listed on the Indonesia Stock Exchange in 2020 that are classified as manipulator, in 2021 there will be 2 (two) companies, and in 2022 there will be 1 (one) company classified as manipulator. Then companies that are classified as non manipulator in 2020 there will be 14 (fourteen) companies, in 2021 there will be 14 (fourteen) companies, and in 2022 there will be 12 (twelve) companies. Furthermore, companies that are classified as grey company in 2020 there will be 5 (five) companies, in 2021 there will be 3 (three) companies, and in 2022 there will be 6 (six) companies.